White Evangelical Christian Ideology and the Construction of Whiteness: Lessons for Educators - Miller, Erin; Tanner, Sam; Willis, Rev. Evan; Hancock, Stephen (Journal of Interdisciplinary Studies in Education, 2022)
In this manuscript, we revisit data from a 9-month ethnographic study that examined whiteness in early childhood. Specifically, the study explored the epistemological and ontological reality of three young white children and how they learned to conflate ethnocentric love with whitewashed justice through the lens of their religious upbringing. We theorize how such epistemological and ontological realities of religious ideologies potentially shape the pedagogies of educators who identify themselves as white Evangelical Christians (a demographic that represents over one-third of the total teaching force in the United States). Finally, we suggest how learning from black theologies could offer a way to expand notions of biblical love and justice to encompass those that are rooted in agency, social justice, and explicit attention to systematic oppression.